2021
DOI: 10.1093/mnras/stab341
|View full text |Cite
|
Sign up to set email alerts
|

The kinematics of globular cluster populations in the E-MOSAICS simulations and their implications for the assembly history of the Milky Way

Abstract: We present a detailed comparison of the Milky Way (MW) globular cluster (GC) kinematics with the 25 Milky Way-mass cosmological simulations from the E-MOSAICS project. While the MW falls within the kinematic distribution of GCs spanned by the simulations, the relative kinematics of its metal-rich ($[\rm {Fe}/\rm {H}]>-1.2$) versus metal-poor ($[\rm {Fe}/\rm {H}]<-1.2$), and inner (r < 8 kpc) versus outer (r > 8 kpc) populations are atypical for its mass. To understand the origins of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 148 publications
5
27
0
1
Order By: Relevance
“…Our observation that old, metal-rich globular clusters are more tightly bound to the Milky Way than young, metal-poor globular clusters confirms the importance of accretion for the formation of the Milky Way's globular cluster system. Our inference also supports previous proposals that a large fraction of the Milky Way's metal-poor globular clusters were accreted (e.g., Forbes & Bridges 2010;Forbes 2020;Kruijssen et al 2019aKruijssen et al ,b, 2020Massari et al 2019;Trujillo-Gomez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observation that old, metal-rich globular clusters are more tightly bound to the Milky Way than young, metal-poor globular clusters confirms the importance of accretion for the formation of the Milky Way's globular cluster system. Our inference also supports previous proposals that a large fraction of the Milky Way's metal-poor globular clusters were accreted (e.g., Forbes & Bridges 2010;Forbes 2020;Kruijssen et al 2019aKruijssen et al ,b, 2020Massari et al 2019;Trujillo-Gomez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…(e.g., Kruijssen et al 2019aKruijssen et al ,b, 2020Pfeffer et al 2020;Trujillo-Gomez et al 2021). When applied to the Milky Way, that formalism can quantify the properties of massive satellite galaxies that have since merged with the Milky Way (e.g., Myeong et al 2018;Hughes et al 2019;Kruijssen et al 2019bKruijssen et al , 2020Pfeffer et al 2020;Trujillo-Gomez et al 2021). Moreover, efforts have been made to match the kinematics of clusters to stellar streams associated with known accretion events.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations have shown that the diversity in age-metallicity relations of Milky Way-mass galaxies results from different assembly histories and can therefore be used to infer such assembly histories (Kruijssen et al 2019a(Kruijssen et al , b , 2020. The simulations have also been shown to reproduce the observed kinematics of the Galactic GC population (Trujillo-Gomez et al 2021 ) and have been used to conclude that GCs associated with stellar streams will be, on average, younger than the GC population not associated with a stellar stream (Hughes et al 2019 ), a result subsequently confirmed through observations of stellar streams in the halo of M31 (Mackey et al 2019 ). Finally, Pfeffer et al ( 2019 ) showed that the simulations reproduce the properties of young cluster populations, and the simulations were subsequently used to predict when and where GCs formed (Reina-Campos et al 2019 ;Keller et al 2020 ).…”
mentioning
confidence: 82%
“…Additionally, the model has allowed the use of GC populations to trace the formation and assembly history of their host galaxy (e.g. Kruijssen et al 2019a;Hughes et al 2019;Pfeffer et al 2020;Trujillo-Gomez et al 2021). We have recently applied these insights to the GC population of the Milky Way, resulting in the quantitative reconstruction of its merger tree (Kruijssen et al 2019b(Kruijssen et al , 2020.…”
Section: The E-mosaics Modelmentioning
confidence: 99%